Revitalization of waste bank management in Cecelan Hamlet, Magelang Regency - Norma Dewi Shalikhah; Dika Satria Bagus Panuntun; Muhamad Aulya Zulkarnain; Maftukhatun Nikmah; Wahyu Dwi Antara; Rizal Maulana Rajib (Universitas Muhammadiyah Magelang, 2024)
Established in 2016, Bank Sampah Lestari, a community-based waste bank, was forced to cease operations due to the COVID-19 pandemic. This outreach initiative aimed to revitalize waste management activities at Bank Sampah Lestari. Employing a Participatory Rural Appraisal (PRA) approach, the project encompassed a series of activities, including raising awareness about the crucial role of waste banks, guiding participants in waste sorting practices, facilitating the sale of paper and cardboard waste, teaching organic fertilizer production, promoting maggot cultivation, encouraging the creation of handicrafts from plastic waste, and supporting vegetable gardening within the bank's premises. The project's outcomes included: 1) the establishment of a new organizational structure for bank sampah membership, 2) the resumption of waste sorting, collection, and sales activities, and 3) enhanced community creativity and knowledge regarding waste management practices.